Penerapan aXe DevTools untuk Mengidentifikasi Pelanggaran Aksesibilitas Website Pemerintah Kabupaten X sesuai Prinsip WCAG 2.1 - Muhammad Sholikhan; Edy Siswanto; Richma Hidayati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify accessibility violations on the official website of the X Regency Government by referring to the Web Content Accessibility Guidelines (WCAG) 2.1 AA level standards. The study adopts a descriptive quantitative method with a case study approach. Testing was conducted through an audit using aXe DevTools on the website's main page, so that each finding could be classified based on four accessibility principles: Perceivable, Operable, Understandable, and Robust (POUR). The test results showed 35 accessibility violations, consisting of 17 Critical categories and 18 Serious categories. No violations were identified under the Moderate or Minor categories. The largest finding was in the Perceivable principle, specifically related to the lack of alternative text on image elements and low color contrast. In addition, in the Operable principle, problems were found in the form of links without clear descriptive text and difficulties in using keyboard-based navigation. These accessibility issues suggest that the website does not fully comply with WCAG 2.1 AA standards, which may hinder inclusive access to public digital services. Thus, the level of accessibility compliance of the X Regency Government website is still not optimal. Improvements need to be made through technical and policy approaches. From a technical perspective, developers must ensure the addition of appropriate alternative text, improvements to color contrast ratios, and optimization of link structures and navigation features. From a policy perspective, continuous training for developers and sustainable governance measures are crucial to maintaining accessibility compliance. By strengthening developer capacity and implementing sustainable policies, local government websites can move towards more inclusive, responsive, and user-friendly digital public services for all users, including those with disabilities. In conclusion, this study highlights the importance of accessibility